Dimensions of Masjid architecture: perspectives and writings in theory and design - Mohd Nawawi, Norwina; Jahn Kassim, Puteri Shireen; Mansor, Ibrahim; hajeedar, Abdul majid; Mohd Rasdi, Mohd Tajuddin; Nik Mohammad, Nik Arshad; Nik Mohd Yusof, Nik Amirul Faiz; Rashid, Mizanur; Hamat, Sufian; Abdul Majid, Noor Hanita; Abdullah, Fadzidah; Ibrahim, Mohd Najib (Kulliyyah of Architecture and Environmental Design, IIUM, 2016)
The book is a culmination of writings from selected practitioners and academics initiated from the elective course of AAR 4033 Masjid Architecture for the Bachelor of Architecture programme in the International Islamic University Malaysia in 2008. The book covers both the theory and design of Masjid Architecture providing perspectives in discussive writings of concepts and approach; evaluation of designs through spatial, tectonic, details and environment; experimentation with construction; and reflective inference to the Quran and Sunnah on the purpose of its establishment. Selected authors are experts in the industry and the academia. The book intend to bridge the gap between theory and design of Masjid least discuss and bring another dimension in reliving the spirit manifested in the establishment of masjid appropriate for the House of Allah.